PENERAPAN PRAKTEK PEMBELAJARAN BERMAKNA BERBASIS BETTER TEACHING LEARNING (BTL) PADA MATA KULIAH MICROTEACHING UNTUK MENGEMBANGKAN KOMPETENSI PROFESIONAL CALON GURU - Sri Sukaesih; Siti Alimah (Jurnal Penelitian Pendidikan, 2012)
Better Teaching and Learning (BTL) developed by the Decentralized Basic Education (DBE). USAID Indonesia DBE Program is a joint program between the Government of Indonesia and the Government of the United States that aims to support the government in improving the quality and relevance of education in Indonesia. The purpose of this study was to investigate the application of meaningfull learning practice based on Better Teaching Learning (BTL) in microteaching course on professional competence in developing prospective teachers. Sampling in this study conducted with a purposive sampling technique. The results showed that the application of meaningfull learning practice based on BTL to develop professional competency prospective teachers, with a mean score achieved was 74% (excellent), 22% (good). Meaningfull learning-based Better Teaching Learning (BTL), recommended to be applied in the education and training of the teaching profession, and can be used as an innovative strategy to improve the quality of the learning process.